IL-12p35 Inhibits Neuroinflammation and Ameliorates Autoimmune Encephalomyelitis - Choi, Jin Kyeong; Dambuza, Ivy M.; He, Chang; Yu, Cheng-Rong; Uche, Anita N.; Mattapallil, Mary J.; Caspi, Rachel R.; Egwuagu, Charles E. (Frontiers in Immunology, 2017)
Multiple sclerosis (MS) is an inflammatory demyelinating disease in which cytokines produced by immune cells that Multiple sclerosis (MS) is an inflammatory demyelinating disease in which cytokines produced by immune cells that infiltrate the brain and spinal cord play a central role. We show here that the IL-12p35 protein might be an effective Biologic for suppressing neuroinflammatory responses and ameliorating the pathology of experimental autoimmune encephalomyelitis (EAE), the mouse model of human MS. We further show that IL-12p35 conferred protection from neuropathy by inhibiting the expansion of pathogenic Th17 and Th1 cells and inhibiting trafficking of inflammatory cells into the brain and spinal cord. In addition, in vitro exposure of encephalitogenic cells to IL-12p35 suppressed their capacity to induce EAE by adoptive transfer. Importantly, the IL-12p35-mediated expansion of Treg and Breg cells and its amelioration of EAE correlated with inhibition of cytokine-induced activation of STAT1/STAT3 pathways. Moreover, IL-12p35 inhibited lymphocyte proliferation by suppressing the expressions of cell-cycle regulatory proteins. Taken together, these results suggest that IL-12p35 can be exploited as a novel Biologic for treating CNS autoimmune diseases and offers the promise of ex-vivo production of large amounts of Tregs and Bregs for immunotherapy.